Realization of a magneto-optical near-zero index medium by an unpaired Dirac point - Zhou, Xin (2018)
We realize an unpaired Dirac cone at the center of the Brillouin zone, using a gyromagnetic photonic crystal with broken square sublattice symmetry and broken time-reversal symmetry. The behavior of the Dirac modes can be described by a gyromagnetic effective medium model with near-zero refractive index, and Voigt parameter near unity. When two domains are subjected to opposite magnetic biases, there exist unidirectional edge states along the domain wall. This establishes a link between topological edge states and the surface waves of homogeneous magneto-optical media.